Analysis of Multi-Server Priority Queueing System with Hysteresis Strategy of Server Reservation and Retrials - Alexander Dudin; Sergey Dudin; Rosanna Manzo; Luigi Rarità (Mathematics, 2022)
A multi-server queueing system with two types of requests and preemptive priority of one type is considered as a model of a cell of a cognitive radio system under practical suggestions about the arrival flows. A hysteresis type strategy for server reservation is suggested to mitigate the effect of interruption of service of low priority requests. Under the arbitrarily fixed values of the sets of the thresholds defining this strategy, the behavior of the system is described by a level-dependent multi-dimensional Markov chain. Formulas for computation of values of performance characteristics of the system are derived. Numerical examples illustrating the dependence of the main performance characteristics on the thresholds defining the strategy of control and the numerical solution of the problem of the optimal choice of the thresholds are reported.